The 'Frankenstein' of Industrial Development: Differentiation and Interest Groups within Healthcare Industry - Por Heong Hong (Kajian Malaysia, 2011)
As studied elsewhere, other than providing in-service education for its members and functioning as a medium of professional control by establishing general standards of conduct, professional associations also work to uphold and protect the interests of their members. Professional bodies are thus both the product of and the driving force for professionalisation and the consolidation of professional interest. Bred within the historical context of the cultural and social collision between local, traditional authority and western colonial power in the last two centuries, the development of the (westernbased) medical profession in Malaya (known as Malaysia from 1963 onwards and thus shall be used for entire article) shares many similarities with its western counterparts in terms of professionalisation. The establishment of the Straits Medical Association (SMA) in 1890 by a group of medical officers, all foreign, was one effort to advance the development of the profession and cater to the need for in-service education in the medical community. The association, renamed as the Malayan Medical Association (MMA) in 1959, was the sole official representative for the medical profession in Malaysia from the post-war years until the 1980s, when the launching of privatisation under the Mahathir administration led to differentiation within the healthcare industry. The emergence of managerialism and the growth of bureaucratisation within the modern hospital setting in the past three decades have added further to the tension between different medical groups in the healthcare industry. By investigating the development of different medical and paramedical groups, this paper aims to capture the main contention between these groups and explain the meaning of interest pluralisation in the Malaysian healthcare industry. This paper argues that differentiation and interest pluralisation are inevitable outcomes of industrial development and require democratisation as a resolution to the conflict between different interest groups.